2017
DOI: 10.1111/tbj.12766
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Breast Carcinoma in Cerebrospinal Fluid: A Cytopathological Review of 15 Cases

Abstract: The incidence of metastatic carcinoma to the meninges ("meningeal carcinomatosis" [MC]) is increasing due to longer survival of patients and improved imaging techniques. Currently, MC is best diagnosed by cytopathological evaluation of cerebrospinal fluid (CSF). Breast primaries are the commonest cause of MC; although cytopathological features thereof have not been, as yet, fully characterized. In this study of meningeal mammary carcinomatosis, relevant clinicopathological data and archived cytopathological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…In breast carcinoma, there are several routes that carcinoma cells can potentially take to involve the meninges. Such involvement can follow metastasis to: (i) the meninges, (ii) brain parenchyma, (iii) axial bones, (iv) choroid plexus, or (v) cranial nerves (8). Most cases of EMPD brain metastasis show disseminated lesions, resulting mainly from intraspinal axial bone metastasis.…”
Section: Meningeal Carcinomatosis In Advanced Extramammary Paget's DImentioning
confidence: 99%
“…In breast carcinoma, there are several routes that carcinoma cells can potentially take to involve the meninges. Such involvement can follow metastasis to: (i) the meninges, (ii) brain parenchyma, (iii) axial bones, (iv) choroid plexus, or (v) cranial nerves (8). Most cases of EMPD brain metastasis show disseminated lesions, resulting mainly from intraspinal axial bone metastasis.…”
Section: Meningeal Carcinomatosis In Advanced Extramammary Paget's DImentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) analysis for cytopathological diagnosis plays a pivotal role in the diagnosis and management of a wide array of neurological disorders, including infections, [1][2][3][4][5][6] neoplasms, and inflammatory conditions. The cytopathologic examination of CSF specimens offers a minimally invasive means of obtaining valuable diagnostic information, aiding in the identification of abnormal cells, infectious agents, and other pathological processes within the central 1,3,4,[7][8][9][10][11][12][13][14][15] nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…CSF cytopathological evaluation is compulsory in suspected inflammatory, neoplastic, or hemorrhagic conditions and needs to be interpreted in the clinical [3][4][5][7][8][9][10][11][12][13][14][15][16] context.…”
Section: Introductionmentioning
confidence: 99%
“…Ho et al ( 11 ) summarized cytomorphological characteristics of primary CNS tumors in the CSF. Rao et al ( 12 ) reported cytopathological characteristics of CSF for 15 patients with breast cancer. Bell ( 13 ) reported the pitfalls which could interfere with the diagnostic accuracy in CSF cytology Bigner ( 14 ) comprehensively summarized CSF cytology from the preparation method to the cytological findings of non-infectious condition, infectious conditions, hematopoietic tumors, metastatic carcinomas and primary CNS tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of characteristics of leukocytes, the findings have been evaluated manually in cytological specimens. For example, lymphocytes and monocytes mixed with erythrocytes and fibrin are observed in the background of metastatic breast cancer specimens ( 12 ), neutrophils are identified in malignant specimens of the central nervous system and eosinophils have been reported in patients with Hodgkin's lymphoma ( 5 ). Moreover, reactive and inflammatory infiltrates have been reported in the background when only a few metastatic cancer cells are detected in CSF ( 14 ).…”
Section: Introductionmentioning
confidence: 99%